Pengelolaan Arsip Statis di Record Centre Fakultas Ilmu Komunikasi Universitas Padjadjaran - Fitria, Winda Nur; Sukaesih, Sukaesih; Sujana, Lusi Romaddyniah (Ilmu Informasi Perpustakaan dan Kearsipan, 2023)
The research aims to determine the management of static archives at Padjadjaran University's Record Center of the Faculty of Communication Sciences. This study employs qualitative research with a descriptive research design. The informant in this study was the head of the Record Center archive at Padjadjaran University's Faculty of Communication Sciences. Data collection methods include observation, interviews, and literature reviews. Recording, grouping, and depreciating archives are examples of inactive static archive management activities. Based on the findings, it is possible to conclude that the management of static archives at the Record Center of the Faculty of Communication Sciences, Padjadjaran University is going well, but there are still a few things that could be better.